Dipeptidyl peptidase 4 (DPP-4) is expressed in mouse and human islets and its activity is decreased in human islets from individuals with type 2 diabetes. - Omar, Bilal; Liehua, Liu; Yamada, Yuchiro; Seino, Yutaka; Marchetti, Piero; Ahrén, Bo (Diabetologia, 2014)
Inhibition of the enzyme dipeptidyl peptidase 4 (DPP-4), which cleaves and inactivates glucagon-like peptide 1 (GLP-1), is a glucose-lowering strategy in type 2 diabetes. Since DPP-4 is a ubiquitously distributed enzyme, we examined whether it is expressed in islets and whether an islet effect to inhibit DPP-4 may result in stimulated insulin secretion.